(untitled) (Conferencea, 2024)
In this article, the speech characteristics of children with autism syndrome The real problem in the development of household corrective pedagogical work, the creation of a comprehensive system of psychological and pedagogical support for children with autism, and the lack of formation of the communicative function of speech as a reflection of the specific characteristics of autism are presented. Speech in autism to consider the manifestation of disorders; based on the special educational needs of autistic children, to determine the characteristics of speech therapy work with children of this category in the system of psychological and pedagogical support for them; autistic information on the acquisition of practical skills of the influence of speech therapy on children’s speech is given.